Changing Power of Journalism: The Two Phases of Mediatization. Issue 4 (4th July 2016) - Kunelius, Risto; Reunanen, Esa
Abstract: Current conceptualizations of mediatization, particularly the mediatization of politics, stem largely from the imaginaries of the mass media era. This article questions the validity of these conceptualizations in the contemporary, more diffuse media environment. It argues that we are entering a new phase of mediatization in which journalism—as a core institution of the media—itself struggles with the effects of mediatization. Bringing together the discussions of mediatization and the "crisis of journalism, " the article suggests that a system theory based approach that understands mediatization as a process in which the construction of "public attention" changes its role in the coordination of institutional action can capture journalism's role both in the mass media era and in the present media environment.